The characteristic Performace of Quantitative Flowering Characters and Metabolomic Profile of Shallot (Allium cepa var. aggregatum) Induced by Vernalization - Marlin; Maharijaya, Awang; Sobir; Purwito, Agus (Jurnal Hortikultura Indonesia (JHI), 2018)
Flowering initiation is regulated by the internal and external condition of plant. Vernalization is considered to induce flower initiation on shallots (Allium cepa var. aggregatum). This research objective was to analyze the flowering quantitatif characters and metabolomic profile of shallot during vernalization on bulb development. Vernalization was carried out at 8 0C for 6 weeks treatment were four bulb growth stage i.e non-vernalized bulbs (S0), vernalization on embryonic stage (S1), vernalized bulbs on 1 cm of shoot stage (S2) and vernalized bulbs on 2 cm of shoot stage (S3). Vernalization treatment in early stage increased the number of tillers, number of umbel, diameter of umbel and percentage of flowering compared to another stage. The early stage of bulbs growth was the effective stage in receiving vernalization treatment. The bigger number and diameter of umbel lead to the higher percentage of flowering in shallot plant. The number and diameter of umbel can be used as character of selection for the percentage flowering character in shallot. Metabolomic analysis has identified of 104 specific metabolites from different vernalization treatments and clustered shallot into three groups. The early stadium of bulbs development (embryo stadia and stadia 1 cm buds) contains specific metabolomes (phytol and 2-propanone) as the indicator of reproductive phase. Keywords: correlation, flower induction, hierarchical cluster analysis, metabolomic